(3QHhGJ GdbQV hQHhGJ GdHjY (B/s - (3Jhajb QVG, MSjfs ([(3Ohf ecGf(B]: s [(3Ohf fGTQ(B], s, 1998)
(3CUhd GdQHhGJ (B1-(3CUhd GdQHhGJ aj GdGSdGe (B2- (3GdGMcGe GdebGQfI hhLgGJ GdeMOKjf (B3- (3QHG GdbQhV (B4- (3GdGSJOGfI HGdQHG (B5- (3GdeWGdHI HGdOjf hJCLjdg (B6-(3JYOjd GdOjf (B7-(3ehGVY GdQHG aj GdbhGfjf GdeYGUQI (B8-(3QHhGJ GdHjY (B9-(3QHG GdaVd (B10-(3JMQje HjY eG CTJQj bHd ajVg (B11- (3JMQje dHY GdcGdF HGdcGdFs
Keywords: (3GdQHGs; (3GdeYGedGJ GdHfcjIs; (3QHhGJ HjYs; (3QHhGJ bQhVs